Influence of Rheum taxa and harvesting date on the content of L-ascorbic acid and oxalic acid in the climatic conditions of South Moravia (Czech Republic) - Neugebauerová, Jarmila; Hakalová, Eliška; Nedorost Ragasová, Lucia; Čechová, Jana; Raddová, Jana; Tekielska, Dorota Anna; Pokluda, Robert (Polish Society for Horticultural Science, 2023)
Rhubarb (Rheum L.) is a well-known medicinal and culinary plant. Apart from its rich nutritional value, rhubarb contains a higher concentration of oxalates. In this study, the content of L-ascorbic acid (AA) and oxalic acid (OA) within three rhubarb species (Rheum rhabarbarum, R. rhaponticum and R. palmatum x wittrockii) differentiated to 16 accessions in a gene bank rhubarb collection (Lednice, Czech Republic) in the condition of conventional production in the South Moravia region during the harvesting period was evaluated. While L-ascorbic acid is essential in human nutrition, oxalic acid is considered toxic, and high doses may cause serious health issues. AA and OA content, the morphology evaluation and ISSR (inter simple sequence repeats)-based genetic analysis were performed. The results of this study confirm the significant influence of taxonomy and harvesting time on the content of AA in Rheum accessions. The content of AA was determined from 6 mg . 100 g-1 to 10 g . 100 g-1 fresh weight (FW) at the beginning of the harvesting season (May) up to 25 mg . 100 g-1 FW at the end of the harvesting period. The content of OA strongly varied from 300 mg . 100 g-1 to 1800 mg . 100 g-1 FW. Regarding the antinutrient character of oxalate, the optimal harvest period of this region was estimated to be from May to early June, when the OA content was the lowest. The role of AA as a precursor of oxalate formation in rhubarb was not affirmed by the results of this study.
Keywords: Chinese rhubarb; gene bank collection; genotypes; ISSR analysis; oxalate; rhubarb; vitamin C